PERENCANAAN KURIKULUM BERBASIS PESANTREN DI SEKOLAH MENENGAH KEJURUAN - Zainal Abidin; Nur Rokhmatulloh; Moh. Wardi (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2021)
Curriculum planning is an idea that is agreed upon and used as a standing reference in an organization for the process of achieving the goals of the institution. Therefore, the curriculum needs to be carefully planned so that it can answer the needs of all parties and the expectations of educational institutions from all levels and types of education. This paper tries to make the concept of pesantren-based curriculum planning in Vocational High Schools. The planning concept begins with identifying philosophical principles, sociological principles and psychological principles. These three principles serve as a basis for formulating student output, determining subjects, teaching resources, designing learning experiences and determining evaluation tools.